PERLINDUNGAN HUKUM DAN HAK ASASI MANUSIA BAGI MASYARAKAT PAPUA (KABUPATEN PANIAI) - Suryono, Kelik Endro (Juris Humanity: Jurnal Riset dan Kajian Hukum Hak Asasi Manusia, 2022)
The purpose of this research is to find out cases of violations related to human rights in Papua and to find out the state's responsibility for violations of human rights in Paniai Regency, Papua Province. The formulation of the problem in this study is why the issue of human rights violations in Paniai District, Papua Province has occurred again and what is the role of the state in protecting human rights in Indonesia and what is the international view of the state's role in protecting human rights in Indonesia. The purpose of this study is to determine the role of the state in protecting human rights in Indonesia and to find out the legal view of the state's role in protecting human rights in Indonesia. The research method used in this study is a normative research method with primary data sources derived from library research. This research was conducted using a statutory approach in order to further study the legal basis by examining laws and regulations related to human rights violations that occurred in Paniai district, Papua. The findings in this study are that the role of the state in protecting human rights in Indonesia has been considered in such a way as can be seen from the many laws and regulations regarding human rights whose aim is to protect the rights of the humans themselves. However, the issue of resolving human rights cases must be carried out as fairly and transparently as possible in their settlement, considering the obligation of the state to carry out its role as a protector of human rights for all of its people, must be maximized and every right must be fulfilled. However, in practice discrimination against human rights is still widely encountered due to injustice that comes from the authorities themselves. Keyword : HAM, Paniai, Accountability and justice